2008
DOI: 10.4049/jimmunol.181.9.6101
|View full text |Cite
|
Sign up to set email alerts
|

An Epithelial Progenitor Pool Regulates Thymus Growth

Abstract: Thymic epithelium provides an essential cellular substrate for T cell development and selection. Gradual age-associated thymic atrophy leads to a reduction in functional thymic tissue and a decline in de novo T cell generation. Development of strategies tailored toward regeneration of thymic tissue provides an important possibility to improve immune function in elderly individuals and increase the capacity for immune recovery in patients having undergone bone marrow transfer following immunoablative therapies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 36 publications
4
58
0
1
Order By: Relevance
“…42,43,48 Our results clearly indicate that Wnt4 regulates the number of TECs in the thymus and consequently the number of intrathymic niches available for thymus-seeding progenitors ( Figures 4A, 5A, and 6). Conversely, Wnt4 also is capable of directly influencing the expansion of the most immature cKit hi thymocytes in vitro ( Figure 3C-D).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…42,43,48 Our results clearly indicate that Wnt4 regulates the number of TECs in the thymus and consequently the number of intrathymic niches available for thymus-seeding progenitors ( Figures 4A, 5A, and 6). Conversely, Wnt4 also is capable of directly influencing the expansion of the most immature cKit hi thymocytes in vitro ( Figure 3C-D).…”
Section: Discussionmentioning
confidence: 60%
“…38,40 Wnt4 regulates TEC numbers during fetal thymopoiesis and postnatal thymic expansion Although our results indicate that Wnt4 has a direct effect on ETP and DN2 numbers, such an early defect would not be sufficient to explain a 2-fold difference in total cellularity because it should be compensated for at later stages. 41 Given that the early stages of T-cell development are highly dependent on the availability of stromal niches, 42 and because the number of TECs has been suggested to be the limiting factor in determining thymic size, 43 we hypothesized that Wnt4 also could have an autocrine effect on TEC development. Indeed, there were fewer TECs per thymus already on E15.5 in the Wnt4 Ϫ/Ϫ thymus and the relative difference remained the same on E18.5 ( Figure 4A).…”
Section: Wnt4 In Fetal and Postnatal Thymopoiesis 5167mentioning
confidence: 99%
“…It is well accepted that mTECs and cTECs share a common bipotent progenitor (TEPC) during thymus organogenesis (Rossi et al, 2006), and this progenitor pool lasts for a very long time after birth to support continuous TEC generation and homeostasis (Bleul et al, 2006). Though little is known about the characterization of these TEPCs, the size of the TEC progenitor pool signifi cantly controls the number of mature TECs and limits their recovery (Jenkinson et al, 2008). Once the progenitor pool was ruined during embryogenesis, postnatal TECs could not be fully recovered.…”
Section: Thymus Organogenesis and Tec Developmentmentioning
confidence: 99%
“…For example, gene mutation or deletion of the forkhead transcription factor Foxn1 in human or mouse affects thymic epithelial differentiation, resulting in loss of intrathymic T-cell development and severe immunodeficiency Chidgey etal., 2007). Furthermore, reductions in the number of TECs results in a reduced number of thymocytes (Jenkinson et al, 2008;Jenkinson et al, 2007;Revest et al, 2001). Many studies have demonstrated that during aging, TECs undergo both a qualitative and quantitative loss believed to be one of the major factors responsible for age-dependent thymic involution (Dorshkind et al, 2009;Zediak and Bhandoola., 2005;Lynch., 2009;Taub and Longo., 2005).…”
Section: Introductionmentioning
confidence: 99%